CO2 geological storage site selection and long-term potential assessment framework based on TOUGH2/ECO2N - Wenjie Sun; Wen Liu; Shunli Ren; Gang Lin; Chenxu Wang; Xiaodong Jiang (PLoS ONE, 2025)
Carbon dioxide capture and storage (CCS) technology is considered a crucial tactic for achieving the “dual carbon” goals. However, current CCS technologies face several challenges, such as the absence of a comprehensive and systematic set of criteria for site selection, coupled with the lack of a universally applicable evaluation framework.To address these issues, this study proposes a regional-scale CO2 geological storage suitability assessment and potential estimation framework that can be adapted to similar regions. Using the Yellow River Delta as a case study, a geological storage site selection indicator system was developed, and a model for assessing site suitability was constructed.The model was employed to evaluate the appropriateness of CO2 geological sequestration sites within the study region, and numerical simulations of CO2 storage were performed utilizing the TOUGH2/ECO2N simulator for prospective target zones. This research examines the migration dynamics of CO2 in saline aquifers, the progression of storage mechanisms, and the carbon sequestration capacity of various storage configurations. The research addresses key questions such as: How can the optimal CO2 geological storage target area be selected? How can the best storage strategy matching the target area be determined? How can the migration and distribution characteristics of CO2 after storage be simulated? Are there potential risks in the future?